A retrospective study of treatment and outcomes in synchronous systemic and central nervous system large B-cell lymphoma - Haydu, J. Erika; Redd, Robert A.; Lei, Matthew M.; Hochberg, Ephraim P.; Barnes, Jeffrey A.; Armand, Philippe; Soumerai, Jacob D.; Eichler, April F.; Jacobsen, Eric D.; Jordan, Justin T.; Jacobson, Caron A.; LaCasce, Ann S.; et al. (Blood Advances, 2026)
Synchronous systemic and de novo secondary central nervous system (CNS) large B-cell lymphoma (LBCL) is an aggressive clinical entity with a historically poor prognosis. Given the rarity of this presentation, prospective studies are limited, and treatment paradigms and outcomes are extrapolated from small, heterogenous retrospective studies. We performed a retrospective study with extended follow-up for 63 consecutive patients with previously untreated synchronous systemic and de novo secondary CNS LBCLs presenting to 2 institutions over 21 years. Most patients had diffuse LBCL (73%) and were treated with an average of 6 cycles of R-CHOP (rituximab, cyclophosphamide, doxorubicin, Oncovin [vincristine], and prednisone) intercalated with high-dose IV methotrexate (R-CHOP-M). The overall response rate was 84% (75% complete). With a median follow-up of 8.1 years, the median progression-free survival (PFS) was 1.2 years, and the 6-year PFS rate was 37%. The median overall survival (OS) was 7.9 years, and the 6-year OS rate was 52%. Normal lactate dehydrogenase (LDH), low International Prognostic Index (IPI) score, and brain parenchymal-only CNS disease were associated with improved PFS, whereas normal LDH and parenchymal disease were associated with OS. The 25% of patients who underwent consolidation with high-dose chemotherapy (HDC) and autologous stem cell transplant (ASCT) had superior PFS and OS than patients who did not receive a transplant, with particular benefit in those with IPI score of ≥3. This study demonstrates that a proportion of patients presenting with secondary CNS involvement are cured with upfront chemoimmunotherapy with or without HDC/ASCT and helps identify prognostically favorable subgroups, which can guide counseling of patients with this rare, high-risk clinical presentation.
CRIS-Team Scopus Importer:2026-01-26